Exploring Financial and Digital Literacy: How Technology Adoption Attitude Drives Mobile Service Innovation in Cirebon MSMEs - Mardiyani Mardiyani; Siska Ernawati Fatimah; Acep Komara (School of Business, IPB University (SB-IPB), 2026)
Background: Financial and digital literacy are key factors in technology adoption among MSMEs. However, most studies still focus on usage intentions or frequency rather than innovative behavior. It is also important to study MSMEs in Cirebon because of their limited digital infrastructure, varying financial capabilities, and the prevalence of small-scale businesses, all of which influence technology adoption behavior.Objective: To analyze the influence of digital and financial literacy on mobile service innovation, with the mediating of technology attitudes adoption, among MSMEs in Cirebon.Design/Methodology/Approach: Data were collected via a questionnaire administered to 200 SMEs in the culinary, fashion, service, and handicraft sectors using purposive sampling, with the criteria being MSMEs that use digital technologies such as digital marketing, financial transactions, and customer service. Data analysis was conducted using SEM with SmartPLS 4.0.Findings/Results: Digital and financial literacy significantly influence mobile service utilization through the mediation of technology attitudes adoption. The strongest influence is demonstrated by digital literacy on technology attitudes adoption, highlighting the importance of MSMEs’ ability to use digital technology.Conclusion: There is a need for integrated digital and financial literacy training programs that strengthen technology attitudes adoption. Mobile service providers also need to pay attention to ease of use and education to encourage positive user attitudes.Originality/Value (Current State): This study reveals the mechanisms by which digital literacy and financial literacy shape the use of mobile services through technology attitudes adoption among digitally active SMEs in developing regions, an area previously studied primarily in terms of the intention to use technology. Keywords: digital literacy, financial literacy, technology attitude adoption, mobile service innovation, msmes, omnichannel adoption